1996
DOI: 10.2220/biomedres.17.327
|View full text |Cite
|
Sign up to set email alerts
|

<b>Immunocytochemical localization of lysenin, a novel protein isolated from the coelomic fluid of the earthworm <i>Eisenia </i></b><b><i>foetida </i></b>

Abstract: Lysenin is a novel protein that was purified from the coelomic fluid of the earthworm Eisenia foetida (Lumbricidae), and it causes contraction of the rat aorta (12). The distribution of this protein was examined immunocytochemically in this species and in the earthworm Pheretima c0m1mm.issima (Megascolecidae) with an antiserum raised in rabbit against lysenin. A positive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…We first examined the levels of sphingomyelin on the surface of proliferating C2C12 cells maintained in high-serum medium by probing fixed cells with 0.5 mg/ml lysenin. Subsequent immunostaining using a specific anti-lysenin antibody (Sekizawa et al 1996) showed that sphingomyelin on the surface of proliferating C2C12 cells was barely detectable (Figures 1A and 1B and quantified in Figure 2A). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first examined the levels of sphingomyelin on the surface of proliferating C2C12 cells maintained in high-serum medium by probing fixed cells with 0.5 mg/ml lysenin. Subsequent immunostaining using a specific anti-lysenin antibody (Sekizawa et al 1996) showed that sphingomyelin on the surface of proliferating C2C12 cells was barely detectable (Figures 1A and 1B and quantified in Figure 2A). …”
Section: Resultsmentioning
confidence: 99%
“…For BrdU detection, cells were then treated with 3 N hydrochloric acid for 10 min at room temperature. Cells were then incubated with primary antibodies (mouse monoclonal anti-MyoD clone 5.8A [Dakocytomation; Carpinteria, CA]), anti-myogenin clone F5D (a gift from Dr. W. Wright at University of Texas), anti-sarcomeric myosin heavy chain (sMyHC) clone MF20, anti-BrdU clone G3G4 and anti-PAX7 (Developmental Studies Hybridoma Bank; Iowa City, IA), hamster monoclonal anti-Bcl-2 clone 3F11 (BD Pharmingen; San Diego, CA), and rabbit polyclonal antilysenin (Sekizawa et al 1996) (Peptide Institute Inc; Osaka, Japan). After washes in PBS, primary antibody binding was visualized with Alexa Fluor dye-conjugated secondary antibodies (Molecular Probes; Eugene, OR) for 30 min before washing and mounting in Fluoromount fluorescent mounting medium (DakoCytomation) containing 100 ng/ml 49,6-diamidino-2-phenylindole (DAPI) or Hoechst 33258.…”
Section: Lysenin Probing and Immunostainingmentioning
confidence: 99%
“…The protein yielded a single band after SDS-polyacrylamide gel electrophoresis, and no contaminating protein bands were detected after staining the gel with Coomassie Brilliant Blue. An antiserum against lysenin was raised in male rabbits, as described previously (31), and its specificity was confirmed by immunoblotting analysis, which showed the antiserum recognized only one band of lysenin among all the proteins in the body fluid of E. foetida.…”
Section: Methodsmentioning
confidence: 98%
“…Sections treated with the lysenin antiserum that had been incubated with lysenin showed no evidence of immunoreactivity in all tissues examined. We reported previously that the large coelomocytes were immunoreactive to the lysenin antiserum (Sekizawa et al 1996b).…”
Section: Immunohistochemical Stainingmentioning
confidence: 88%
“…Immunohistochemical staining for light microscopy was performed as described by Sekizawa et al (1996b), with some modifications, using the same lysenin antiserum as used in the cited study. In brief, earthworms were cut into four pieces and fixed in 4% paraformaldehyde for 18 h. After fixation, the tissues were dehydrated through an ethanol series, cleared in xylene, and embedded in paraffin.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%